Design and Synthesis of a Zeolitic Organic Framework. (13th April 2022) - Liu, Yaozu; Chen, Pohua; Wang, Yujie; Suo, Jinquan; Ding, Jiehua; Zhu, Liangkui; Valtchev, Valentin; Yan, Yushan; Qiu, Shilun; Sun, Junliang; Fang, Qianrong
Abstract: The development of novel zeolite‐like materials with large channel windows and high stability is of importance but remains a tremendous challenge. Herein, we report the first example of a 3D covalent organic framework with zeolitic network, namely the zeolitic organic framework (ZOF). By combining two kinds of tetrahedral building blocks with fixed or relatively free bond angles, ZOF‐1 with the zeolitic crb net has been successfully synthesized. Its structure was determined by the single‐crystal 3D electron diffraction technique. Remarkably, ZOF‐1 shows high chemical stability, large pore size (up to 16 Å), and excellent specific surface area (≈2785 m 2 g −1 ), which is superior to its analogues with the same network, including traditional aluminosilicate zeolites and zeolitic imidazole frameworks. This study thus opens a new avenue to construct zeolite‐like materials with pure organic frameworks and will promote their potential applications in adsorption and catalysis for macromolecules. Abstract : The first case of zeolite‐like crystalline porous organic materials, ZOF‐1 with high chemical stability, large pore size (up to 16 Å), and excellent specific surface area (≈2785 m 2 g −1 ) is reported. It is superior to its analogues with the same network, including traditional aluminosilicate zeolites and zeolitic imidazole frameworks.